Impact of physicial activity with programmed intensity in body composition - Beqa, Gentiana; Miftari, Florian; Gjinovci, Bahri; Elezi, Abdulla; Elezi, Gresa (Journal of Education, Health and Sport, 2018)
Physical activity is a very important regulator of body mass, a more natural way of consuming energy which, according to the lifestyle of today, has become very limited. Due to this fact, this research was intended to validate the influence of cyclically-programmed intensity physical activity on some body components. The sample for the purpose of this research included 25 women aged 20-30 who willingly admitted to be part of this research. These variables of body components have been applied: Body weight (WEIG), Body fat (BOFA), Muscle mass (MUMA), Body mass index (BMI) and Visceral fat level (VIFA).For the evaluation of body components, the bioelectric device Tanita BC-60 (Segmental Body Composition Monitor) was used. The women’s group included in the research as an experimental group has undergone a 3-month training program with physical activity with programmed intensity of 50-70% of the heart rate. For the assessment of the difference between two dependent groups in arithmetical averages, the t-testing (Paired Sample T-Test) has been applied. Results obtained after statistical processing show that cyclic physical activity with programmed intensity (50-70%) three times a week for one hour had a positive effect on body fat tissue reduction for 17.79%, p <0.000.